James Edwin Hewitt e o ensino de inglês no século XIX - Santos, Elaine Maria (2020)
During the 19th century, the teaching of English occupied a secondary place in Brazil, in view of the fascination that French caused in the society of the time. It was in this context of superiority of the French language that we can spot the struggles faced by English teachers to prove that studying English could be valuable. Taking that into consideration, this article aims to present the trajectory of the teacher James E. Hewitt, and his attempts to fight for the valorization of English teaching. Based on the assumptions of the New Cultural History, an investigation was carried out in several sources, such as legislation, prefaces of books and newspapers, so that it could be possible to verify his contribution to the educational historiography of the 19th century, and more specifically for the teaching of English in the Collegio de Pedro II, in the final decades of the century.